Intervention of Providing Iron Consumption Education to Prevent the Risk of Bleeding in Mrs. I Spontaneous Postpartum with Anemia - Afni Wulandari; Uni Wahyuni; Nugeraha Risdiyanto; Nadila Nur Azmi; Melati Puspita Sari (Al Makki Health Informatics Journal, 2024)
Postpartum hemorrhage is one of the leading causes of 150,000 maternal deaths each year worldwide, and nearly 4 out of 5 such deaths occur within 4 hours of delivery. One of the factors that can cause postpartum hemorrhage is the presence of anemia in pregnant women, which can be caused by iron and vitamin B12 deficiency. If anemia is not treated during pregnancy, it can impact the postpartum period by increasing the risk of uterine atony and significant bleeding. The purpose of this study was to explain nursing care in postpartum mothers with anemia using an educational intervention of iron consumption to prevent postpartum hemorrhage. The research method used is a qualitative approach with case studies as the main method, using observation sheets, interviews, and documentation studies. The subject of this study was one postpartum maternal patient with anemia at RSUD Waled Cirebon. The results of the case study showed clinical success in the absence of signs and symptoms of bleeding, improvement in the mother's condition, although breast milk expenditure was still not optimal. The implication of this study is that effective nursing care delivery can meet patient needs and prevent further complications such as postpartum hemorrhage.